Digital Theology: Saintly Marvels and God‐talk on Facebook. Issue 1 (13th July 2021) - Alatas, Ismail Fajrie
Abstract: Among Indonesia's traditionalist Muslims, anecdotes of saintly marvels ( karāma ) relating occurrences that contradict reason or human understanding of nature are lodged in everyday conversations. While scholars have noted how recounting and listening to karāma anecdotes is believed by Muslims to transmit the blessing (baraka) of the saints and facilitate their intercession, this article explores such anecdotes' capacity to engender conversations about God and other issues pertaining to religious belief. It does so by observing the circulation of karāma anecdotes among Indonesia's traditionalist Muslims on Facebook and their role in provoking a variety of God‐talk. The circulation of such anecdotes affords their publics with the ability to assent to, engage with, debate, and question theological propositions. Facebook creates the material preconditions for the production and circulation of accessible and shareable karāma anecdotes that enables Muslims beyond the scholastic elites to participate in theological discussion and reflection while facilitating digital practices that can be construed as theologically meaningful. It also facilitates various disputations, including those that are theological, between Muslims adhering to different Islamic currents. Far from simply being a channel of communication or a mode of dissemination, Facebook may indeed come to function as a digital infrastructure of theology.